Cutaneous Infection by Fusarium oxysporum - Pachecho-Rosas, Daniel Octavio; Sámano-Aviña, Mariana Guadalupe; Feregrino, Raúl Romero-; Bonifaz, Alexandro; Santibañez, Javier Araiza-; Herrera-Falcón, Alfredo; Montes-García, Grace Andrea (Archives of Clinical and Medical Case Reports, 2025)
Fusarium is a genus of filamentous fungi that can cause disseminated infections. Fusariosis is the second most common invasive fungal infection in patients with hematological malignancies. Disseminated infections occur specifically in patients with profound neutropenia. Fusarium infections are suspected in those who have had a prolonged fever; other clinical forms include cutaneous, sinusitis, pneumonia, endophtalmitis, and fungemia. Cutaneous fusariosis in immunocompromised patients presents in a disseminated form. The most common lesion in patients with cutaneous involvement are erythematous and painful nodules or papules, with or without central necrosis. In the work, we report a case of cutaneous fusariosis in a pediatric patient, which is rare, with condition that leads to immunosuppression. The presentation was solely cutaneous, which is the least common presentation. It is necessary to determine if there is involvement of different organs. Prolonged treatment is required. More large-scale clinical studies are needed to characterize the optimal antifungal regimen and treatment duration.